Antiplatelet Activity of Tussilagone via Inhibition of the GPVI Downstream Signaling Pathway in Platelets - Zhou, Jing; Yang, Ru-Ping; Song, Wei; Xu, Hui-Min; Wang, Yong-Hui (Frontiers in Medicine, 2020)
Tussilagone is a sesquiterpenoid extracted from Tussilago farfara and is used as an oriental medicine for asthma and bronchitis. Although previous studies have shown that tussilagone has an inhibitory effect on platelet aggregation, no studies have been performed to investigate its precise effect on platelets, and the underlying mechanism remains unclear. In the present study, we showed that tussilagone inhibited platelet aggregation induced by collagen, thrombin and ADP, as well as platelet release induced by collagen and thrombin, in mice. Tussilagone decreased P-selection expression and αIIbβ3 activation (JON/A binding) in activated platelets, which indicated that tussilagone inhibited platelet activation. Moreover, tussilagone suppressed platelet spreading on fibrinogen and clot retraction. The levels of phosphorylated Syk, PLCγ2, Akt, GSK3β and MAPK (ERK1/2 and P38) and molecules associated with GPⅥ downstream signaling were downregulated in the presence of tussilagone. In addition, tussilagone prolonged the occlusion time in a mouse model of FeCl3-induced carotid artery thrombosis and had no effect on mouse tail bleeding time. These results indicate that tussilagone inhibits platelet function in vitro and in vivo and that the underlying mechanism involves the Syk/PLCγ2-PKC/MAPK and PI3K-Akt-GSK3β signaling pathways downstream of GPVI. This research suggests that tussilagone is a potential candidate antiplatelet drug for the prevention of thrombosis.